Mixed motivations and complex causality in the Mekong - Marsh, J (Refugee Studies Centre, University of Oxford, 2015)
Many climate change-affected communities have already been using migration as a means to adapt to and withstand the challenges to their livelihoods and security. Strengthening of existing protections for all migrants is clearly advantageous in the context of climate change